PENGARUH KOMITMEN PEGAWAI, SELF EFFICACY DAN KEPUASAN KERJA TERHADAP PRESTASI KERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA BALIKPAPAN - Didik Hadiyatno; Wiwik Saraswati (UNEJ e-Proceeding)
Towards the Achievement of the Tax Services office employees Work Pratama Balikpapan. The type of research used in this research is explanatory research (explanatory research) with a quantitative approach to explain the relationship between variables through the test of the hypothesis. This Research method using the questionnaire as a tool of data collection are propagated to the 53 respondents as a sample while the population of the 70 respondents from the Tax Services Office employees Pratama Balikpapan, by using multiple linear regression analysis tool. The results of the research conducted, that Commitment Employees have no effect positive and insignificant against the work achievement, Self Efficacy are positive and significant effect against the achievements of the work, and job satisfaction the positive and significant effect against the work achievement. Then the first hypothesis is rejected, the hypothesis into two, three and four are accepted.